In vitro starch digestion in sorghum flour from Algerian cultivars - Souilah, Rachid (BlackWell Publishing Ltd, 2014)
This work aims to evaluate starch digestion in whole sorghum grains. Nine sorghum cultivars were sampled from the Sahara of Algeria. The structural characteristics of sorghum grains were measured. Total starch (TS) varied between 67.67% and 74.82%, digestible starch (DS) between 64.34% and 69.70%, and resistant starch (RS) ranged from 2.55% to 7.98%. The kinetic of starch digestion displayed first-order model. For all sorghum cultivars, starch were digested with different extents, DS at infinite time (D(∞)) ranged from 52.58 to 102.13 g/100 g dry starch, while the hydrolysis index (HI) ranged from 41.55% to 76.93% and high average glycemic index (GI(avg)) ranged from 65.97 to 94.14. The results showed that there are differences in grain quality of Algerian sorghum cultivars. The starch fractions have acceptable nutritional value with good in vitro digestibility characteristics suitable for human health and nutrition.